An Adaptive TDMA Approach for Improving Reliability and Performance in WBAN under Heterogeneous Traffic and Interference - Herculano, Jorge F.; Pereira, Willians de P.; Sá, Alirio S. de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2022)
Medium Access Control (MAC) sublayer approaches based on time division multiple access (TDMA) have been proposed to improve the reliability and efficiency of Wireless Body Area Networks (WBAN). However, these approaches do not adequately deal with the device heterogeneity and the message traffic dynamics in WBANs. This paper proposes a MAC protocol based on an adaptive TDMA policy for WBANs, in which devices receive time slots for transmission, considering their bandwidth demands and communication channel interference conditions. The results show that the proposed approach has superior reliability and performance compared to IEEE 802.15.4, IEEE 802.15.6, and DSBS (Dynamic Scheduling Based on Sleeping Slots) protocols, decreasing message loss while maintaining low power consumption and low latency in all evaluated scenarios.